Analyzing Labor Supply Behavior with Latent Job Opportunity Sets and Institutional Choice Constraints - John K. Dagsvik; Steinar Strøm (Statistics Norway, Research Department, 2003)
In this paper we discuss a general framework for analyzing labor supply behavior in the presence of complicated budget- and quantity constraints of which some are unobserved. The point of departure is that an individual's labor supply decision can be considered as a choice from a set of discrete alternatives (jobs). These jobs are characterized by attributes such as hours of work, sector specific wages and other sector specific aspects of the jobs. We focus in particular on theoretical justification of functional form assumptions and properties of the random components of the model. The paper includes an empirical application based on Norwegian data, in which the labor supply of married women is estimated.
Keywords: J22; C51; 330; Labor supply; non-convex budget sets; non-pecuniary job-attributes; sector-specific wages.